Antibiotic treatment for pneumonia complicating stroke: Recommendations from the pneumonia in stroke consensus (PISCES) group. (December 2019) - Kishore, Amit K; Jeans, Adam R; Garau, Javier; Bustamante, Alejandro; Kalra, Lalit; Langhorne, Peter; Chamorro, Angel; Urra, Xabier; Katan, Mira; Napoli, Mario Di; Westendorp, Willeke; Nederkoorn, Paul J; et al.
Purpose: The microbiological aetiology of pneumonia complicating stroke is poorly characterised. In this second Pneumonia in Stroke ConsEnsuS statement, we propose a standardised approach to empirical antibiotic therapy in pneumonia complicating stroke, based on likely microbiological aetiology, to improve antibiotic stewardship. Methods: Systematic literature searches of multiple databases were undertaken. An evidence review and a round of consensus consultation were completed prior to a final multi-disciplinary consensus meeting in September 2017, held in Barcelona, Spain. Consensus was approached using a modified Delphi technique and defined a priori as 75% agreement between the consensus group members. Findings : No randomised trials to guide antibiotic treatment of pneumonia complicating stroke were identified. Consensus was reached for the following: (1) Stroke-associated pneumonia may be caused by organisms associated with either community-acquired or hospital-acquired pneumonia; (2) Treatment for early stroke-associated pneumonia (<72 h of stroke onset) should cover community-acquired pneumonia organisms; (3) Treatment for late stroke-associated pneumonia (≥72 h and within seven days of stroke onset) should cover community-acquired pneumonia organisms plus coliforms +/− Pseudomonas spp . if risk factors; (4) No additional antimicrobial cover is required for patients with dysphagia or aspiration; (5) Pneumonia occurring after seven days from stroke onset should be treated as for hospital-acquired pneumonia; (6) Treatment should continue for at least seven days for each of these scenarios. Discussion: Consensus recommendations for antibiotic treatment of the spectrum of pneumonia complicating stroke are proposed. However, there was limited evidence available to formulate consensus on choice of specific antibiotic class for pneumonia complicating stroke. Conclusion: Further studies are required to inform evidence-based treatment of stroke-associated pneumonia including randomised trials of antibiotics and validation of candidate biomarkers.